Addressing Global Environmental Security Through Innovative Educational Curricula - Allen-Gil, Susan; Stelljes, Lia; Borysova, Olena (NATO Science for Peace and Security Series C: Environmental Security,, 2009)
As the importance of environmental security increases worldwide, colleges and universities are evaluating how well they are preparing the next generation of environmental scientists and managers and developing new educational approaches. In this volume, we examine: (1) current educational practices and the need for change, (2) educational needs from the perspective of employers and professionals, and (3) new practices in higher education in environmental fields. The contributors were carefully selected by an international coordinating team based on their international reputations in the field of progressive educational approaches and understanding of the global employment market in environmental science. Although the focal geographic areas are North America, Europe and the former Soviet republics, the ideas and strategies discussed are universal to all institutions of higher education. We highlight specific non-traditional approaches such as using the university as a curricular tool, developing permaculture programs, and applying sustainability pedagogy, and document their success from both a student and employer perspective. We also include case studies on risk assessment and eco-efficiency education to illustrate why and how transdisciplinary education can be accomplished. We conclude that it is imperative that our educational systems teach environmental security at the university level within a transdisciplinary context; and that opportunities, such as internships and other methods of applied learning, are included in the curriculum.